Redox topotactic reactions in Fe II - III (oxy)hydroxycarbonate new minerals related to fougèrite in gleysols: "trébeurdenite and mössbauerite" - Génin J.-M.R.; Guérin O.; Herbillon A.J.; Kuzmann E.; Mills S.J.; Morin G.; Ona-Nguema G.; Ruby C.; Upadhyay C. (My University, 2025)
Fougèrite mineral responsible for the bluish-green shade of gleysols in aquifers was identified as Fe II - III oxyhydroxycarbonate, [Fe II 6(1-x)Fe III 6xO 12H 2(7-3x)] 2+ · [CO 2- 3 · 3H 2O] 2- where the average ferric molar fraction x = [Fe III/Fe total] was restricted to the [1/3-2/3] range, up till now. In this paper, Mössbauer spectra of gleys extracted from the schorre of maritime marshes have values of x in the [2/3-1] range. Magnetic properties of homologous chemical compounds studied by Mössbauer spectroscopy are explained with long range order of Fe III ions within Fe cation layers for x = 1/3, 2/3 and 1. Observed values are mixtures of topotactic domains that are in fact minerals with names proposed to IMA: fougèrite for x = 1/3, trébeurdenite for x = 2/3 and mössbauerite for x = 1. © 2012 Springer Science+Business Media B.V.